Grants from Local Governments to the Central Government from the Perspective of the General Principles of Good Governance - Husna, Rizky Wirdatul; Rinaldi, Yanis; Yusri , Yusri (International Journal of Sociology and Law, 2026)
The provision of grants by local governments to vertical agencies of the central government often raises legal tensions over local fiscal autonomy. This study aims to examine the implications of such grant disbursements through the lens of the General Principles of Good Governance (AUPB) and the principles of good financial governance. Employing a normative legal research method, this study analyzes the coherence between the discretionary powers of regional heads and the standards of clean governance. The research findings indicate that grant policies for central government agencies often disregard the principles of prudence and utility, with local budget allocations instead used to fund matters constitutionally the responsibility of the central government (the State Budget). This practice has the potential to become a source of abuse of authority (detournement de pouvoir) if not grounded in objective parameters of local public needs. This study concludes that evaluating grant policies through the AUPB framework, particularly regarding transparency, accountability, and participation, is crucial to preventing local financial subordination. More restrictive regulatory reforms are needed to ensure that grant expenditures remain focused on improving the quality of public services and community welfare at the local level without compromising national fiscal stability.